Resin composition and molded body
The resin composition, featuring a thermoplastic resin, phosphorus flame retardant, and α-olefin/unsaturated carboxylic acid copolymer, addresses the challenge of dispersing phosphorus-based flame retardants, achieving superior flame retardancy and maintaining mechanical properties in molded bodies.
Patent Information
- Application Number
- JP2025012017
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-18
- Filing Date
- 2025-01-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-05-27
AI Technical Summary
Existing resin compositions face challenges in achieving well-dispersed phosphorus-based flame retardants, leading to defective appearances and compromised mechanical properties in molded bodies, while also struggling to balance flame retardancy with maintaining the original physical properties of polyolefin resins.
A resin composition comprising a thermoplastic resin, a phosphorus flame retardant, and a copolymer of α-olefin and unsaturated carboxylic acid, with specific mass ratios that enhance the dispersibility of the phosphorus flame retardant and improve flame retardant properties without deteriorating mechanical properties.
The proposed resin composition achieves excellent flame retardant properties while maintaining the original mechanical properties and bending modulus of polyolefin resins, resulting in a molded body with improved dispersibility and performance.
Smart Images

Figure 2025061872000001 
Figure 2025061872000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a molded article. This application claims priority based on Japanese Patent Application No. 2020-93089, filed in Japan on May 28, 2020, and Japanese Patent Application No. 2021-44430, filed in Japan on March 18, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] Polyolefin resins have excellent mechanical properties (bending properties, tensile properties, etc.), chemical resistance, moldability, etc., as well as a low specific gravity and low cost, so their molded products are used in a variety of applications, including machinery, electrical and electronic equipment, office automation equipment, automotive interior and exterior materials, and electric vehicles. In these applications, the molded articles may be required to have flame retardancy. For example, high flame retardancy is required for molded articles used in housings (frames, cases, exteriors, covers, etc.) for electric / electronic devices and office automation equipment, cables, etc.
[0003] Since polyolefin resins are highly flammable, flame retardants are blended into the molded articles to impart flame retardancy to the resins. Conventionally, flame retardants have been made by combining bromine-based flame retardants with antimony compounds because they are inexpensive and have high flame retardancy. However, due to problems with their persistence in living organisms, phosphorus-based flame retardants have come to be used in recent years. Patent Document 1 proposes a polyolefin resin composition containing two specific phosphorus-based flame retardants.
[0004] On the other hand, Patent Document 2 proposes the use of an alkyl methacrylate polymer mainly composed of an alkyl methacrylate unit having an alkyl group having two or more carbon atoms as a dispersant for polyolefin additives such as flame retardants and crystal nucleating agents, and also proposes a resin composition containing this dispersant, a polyolefin additive, and a polyolefin resin.
[0005] Patent Document 3 proposes a flame-retardant resin composition comprising an olefin polymer, an ethylene polymer containing a maleic anhydride component, and a flame retardant. Patent Document 4 proposes a halogen-free flame-retardant resin composition containing a specific amount of a terpolymer of ethylene, an α-olefin having a polar group, and maleic anhydride, and 180 to 250 parts by mass of a specific amount of a halogen-free flame retardant. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2013-119575 [Patent Document 2] International Publication No. 2011 / 96596 [Patent Document 3] Japanese Patent Application Publication No. 5-117452 [Patent Document 4] Japanese Patent Application Publication No. 2014-91753 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the resin composition described in Patent Document 1 has a problem in that the dispersibility of the phosphorus-based flame retardant is poor, and poorly dispersed phosphorus-based flame retardant is generated in the molded product, resulting in a poor appearance. The resin composition described in Patent Document 2 contains a large amount of dispersant, which may impair the excellent physical properties, such as mechanical properties, of the polyolefin resin.
[0008] It has also been found that the compositions described in Patent Documents 3 and 4 may not be able to provide a molded article having sufficient mechanical strength and flexural modulus while also having high flame retardancy.
[0009] An object of the present invention is to provide a resin composition in which a phosphorus-based flame retardant is well dispersed and which is capable of exhibiting excellent flame retardancy while adequately maintaining the inherent physical properties of a polyolefin resin, and a molded article thereof. [Means for solving the problem]
[0010] The present invention has the following aspects. [1] A resin composition comprising a thermoplastic resin (A), a phosphorus-based flame retardant (B), and a copolymer (C) of an α-olefin and an unsaturated carboxylic acid, wherein the ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) is 5% by mass or more and 400% by mass or less, and the ratio of the copolymer (C) to the phosphorus-based flame retardant (B) is 10% by mass or less. [2] The resin composition according to [1], wherein the proportion of the thermoplastic resin (A) relative to the total mass of the resin composition is 20 mass % or more and 85 mass % or less. [3] The resin composition according to [1] or [2], wherein the copolymer (C) is a copolymer of an α-olefin and maleic anhydride. [4] The resin composition according to any one of [1] to [3], wherein the thermoplastic resin (A) is a polyolefin resin. [5] A molded article made of the resin composition according to any one of [1] to [4]. Effect of the Invention
[0011] According to the present invention, it is possible to provide a resin composition in which a phosphorus-based flame retardant is well dispersed and which is capable of exhibiting excellent flame retardancy while adequately maintaining the inherent physical properties of a polyolefin resin, and a molded article thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Resin composition] A resin composition according to one embodiment of the present invention (hereinafter also referred to as "the resin composition") comprises a thermoplastic resin (A), a phosphorus-based flame retardant (B), and a copolymer (C) of an α-olefin and an unsaturated carboxylic acid, in which the ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) (100 mass%) is 5 mass% or more and 400 mass% or less, and the ratio of the copolymer (C) to the flame retardant (B) (100 mass%) is 10 mass% or less.
[0013] When the present resin composition has the above-described structure, it is possible to obtain a molded article having high flame retardancy with little deterioration in mechanical properties. The copolymer (C) of α-olefin and unsaturated carboxylic acid has a portion having high affinity with each of the thermoplastic resin (A) and the phosphorus-based flame retardant (B), and therefore, by including an appropriate amount of the copolymer (C), the phosphorus-based flame retardant (B) is well dispersed in the thermoplastic resin (A). Therefore, it is possible to prevent the deterioration of mechanical properties due to the aggregation of the phosphorus-based flame retardant (B). On the other hand, the improvement of flame retardancy due to the dispersion effect of the phosphorus-based flame retardant (B) can be expected, but since the copolymer (C) of α-olefin and unsaturated carboxylic acid tends to be easily combusted, if the amount of the copolymer (C) is too much, the copolymer (C) is arranged in large amounts on the surface of the molded body, and the flame retardancy of the molded body is conversely reduced. Therefore, by including the thermoplastic resin (A), the phosphorus-based flame retardant (B), and the copolymer (C) of α-olefin and unsaturated carboxylic acid in appropriate amounts, it is possible to provide a resin composition that can obtain a molded body with high flame retardancy with little deterioration of mechanical properties.
[0014] The present resin composition may further contain a flame retardant or a flame retardant assistant other than the phosphorus-based flame retardant (B). The present resin composition may further contain other components other than those described above, as necessary, within the scope of not impairing the effects of the present invention.
[0015] [Thermoplastic resin (A)] The thermoplastic resin is not particularly limited, and examples thereof include polyolefin resin, polycarbonate resin, polyester resin, acrylonitrile styrene resin, ABS resin, polyamide resin, modified polyphenylene oxide, etc. These may be used alone or in combination of two or more. For example, the thermoplastic resin (A) may be a composite resin of two or more of the above thermoplastic resins.
[0016] The polyolefin resin is not particularly limited, and may be any of the resins described below. The polyester resin is not particularly limited, and may be, for example, polybutylene terephthalate. The polyamide resin is not particularly limited, and may be, for example, nylon 66 or nylon 6. Among them, the present invention is particularly useful when the thermoplastic resin (A) is a polyolefin resin. In the present invention, the term "polyolefin resin" refers to a resin in which the proportion of olefin units or cycloolefin units is 90 mol % or more relative to 100 mol % of all structural units constituting the resin. The proportion of olefin units or cycloolefin units relative to 100 mol % of all structural units constituting the polyolefin resin is preferably 95 mol % or more, and particularly preferably 98 mol % or more.
[0017] Examples of polyolefin resins include α-olefin polymers such as polyethylene, polypropylene, polybutene, poly(3-methyl-1-butene), poly(3-methyl-1-pentene), and poly(4-methyl-1-pentene); α-olefin copolymers such as ethylene-propylene block or random copolymers, α-olefin-propylene block or random copolymers having 4 or more carbon atoms, ethylene-methyl methacrylate copolymers, and ethylene-vinyl acetate copolymers; and cycloolefin polymers such as polycyclohexene and polycyclopentene. Examples of polyethylene include low-density polyethylene, linear low-density polyethylene, and high-density polyethylene. Examples of polypropylene include isotactic polypropylene, syndiotactic polypropylene, hemiisotactic polypropylene, and stereoblock polypropylene. In the α-olefin-propylene block or random copolymers having 4 or more carbon atoms, examples of the α-olefins having 4 or more carbon atoms include butene, 3-methyl-1-butene, 3-methyl-1-pentene, and 4-methyl-1-pentene. These polyolefin resins may be used alone or in combination of two or more kinds.
[0018] The polyolefin resin preferably contains polypropylene. Polypropylene may be used in combination with other polyolefin resins. For example, as the polyolefin resin, a mixture of polypropylene with other α-olefin polymers such as ethylene-propylene block or random copolymers, and α-olefin-propylene block or random copolymers having 4 or more carbon atoms may be used. The polyolefin resin is preferably composed mainly of polypropylene, and the proportion of polypropylene in 100% by mass of the polyolefin resin is preferably 50% by mass or more, and more preferably 60% by mass or more. From the viewpoint of flame retardancy, the polyolefin resin is particularly preferably polypropylene.
[0019] The melt mass flow rate (MFR) of the thermoplastic resin (A) is preferably 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more, while it is preferably 80 g / 10 min or less, more preferably 60 g / 10 min or less. If the MFR of the thermoplastic resin (A) is the lower limit or more, the molding processability is better, and if it is the upper limit or less, the bending properties, tensile properties, chemical resistance properties, etc. are better. The preferable lower limit value and upper limit value can be appropriately combined (the same applies below). The MFR of the thermoplastic resin (A) may be, for example, 0.1 g / 10 min or more and 80 g / 10 min or less, or 0.5 g / 10 min or more and 60 g / 10 min or more. The melt mass flow rate of the thermoplastic resin (A) is measured in accordance with JIS K7210 under conditions of a temperature of 230° C. and a load of 2.16 kg.
[0020] The proportion of the thermoplastic resin (A) relative to the total mass of the resin composition is preferably 20% by mass or more, more preferably 30% by mass or more, more preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more, while it is preferably 85% by mass or less, more preferably 83% by mass or less, and even more preferably 80% by mass or less. If the proportion of the thermoplastic resin (A) is equal to or more than the lower limit, the inherent physical properties of the thermoplastic resin (A) are easily exhibited, and if it is equal to or less than the upper limit, the flame retardancy is more excellent. The proportion of the thermoplastic resin (A) relative to the total mass of the present resin composition may be, for example, 20 mass% or more and 85 mass% or less, 30 mass% or more and 85 mass% or less, 40 mass% or more and 85 mass% or less, 50 mass% or more and 85 mass% or less, 55 mass% or more and 83 mass% or less, or 60 mass% or more and 80 mass% or less.
[0021] [Phosphorus-based flame retardants (B)] The phosphorus-based flame retardant (B) is a phosphorus compound, ie, a compound containing a phosphorus atom in the molecule. The phosphorus-based flame retardant (B) exerts a flame retardant effect by forming char when the resin composition is burned. The phosphorus-based flame retardant (B) may be a known one, and examples thereof include (poly)phosphates and (poly)phosphate esters. "(Poly)phosphates" refers to phosphates or polyphosphates. "(Poly)phosphate esters" refers to phosphate esters or polyphosphate esters. The phosphorus-based flame retardant (B) is preferably a solid at 80°C.
[0022] As the phosphorus-based flame retardant (B), a (poly)phosphate is preferred from the standpoint of flame retardancy. Examples of (poly)phosphates include ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, piperazine orthophosphate, melamine pyrophosphate, piperazine pyrophosphate, melamine polyphosphate, melamine orthophosphate, calcium phosphate, and magnesium phosphate. In addition, in the above examples, compounds in which melamine or piperazine is replaced with other nitrogen compounds can also be used. Examples of other nitrogen compounds include N,N,N',N'-tetramethyldiaminomethane, ethylenediamine, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-diethylethylenediamine, 1,2-propanediamine, 1,3-propanediamine, tetramethylethylenediamine, ethylenediamine, diethyl ... Ethylenediamine, pentamethylenediamine, hexamethylenediamine, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, trans-2,5-dimethylpiperazine, 1,4-bis(2-aminoethyl)piperazine, 1,4-bis(3-aminopropyl)piperazine, acetoguanamine, benzoguanamine, acrylguanamine, 2,4-diamino-6-nonyl-1,3,5-trimethylguanamine, Azine, 2,4-diamino-6-hydroxy-1,3,5-triazine, 2-amino-4,6-dihydroxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-ethoxy-1,3,5-triazine, 2,4-diamino-6-propoxy-1,3,5-triazine, 2,4-diamino-6-isopropoxy-1,3,5-triazine, 2,4-diamino-6-mercapto-1 ,3,5-triazine, 2-amino-4,6-dimercapto-1,3,5-triazine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, melamine pyrophosphate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, and 1,3-hexylenedimelamine.These (poly)phosphates may be used alone or in combination of two or more.
[0023] Among the above, the phosphorus-based flame retardant (B) is preferably a salt of (poly)phosphoric acid and a nitrogen compound (hereinafter also referred to as "compound (B1)"). "(Poly)phosphoric acid" refers to phosphoric acid or polyphosphoric acid. Compound (B1) is an intumescent flame retardant, which forms a surface expansion layer (intemescent) that is a foamed char when the resin composition is burned. The formation of the surface expansion layer suppresses the diffusion and heat transfer of decomposition products, resulting in excellent flame retardancy. Examples of the nitrogen compound in the compound (B1) include ammonia, melamine, piperazine, and the other nitrogen compounds described above.
[0024] Commercially available phosphorus-based flame retardants (B) include, for example, Adeka STAB FP-2100J, FP-2200, and FP-2500S (manufactured by ADEKA Corporation).
[0025] As described above, the ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) (100 mass%) is 5 mass% or more and 400 mass% or less. By having the ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) within this range, when used in combination with the copolymer (C) of an α-olefin and a carboxylic anhydride described below, a significant decrease in mechanical properties and flexural modulus can be prevented and high flame retardancy can be obtained.
[0026] Among the above, the ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) is preferably 10 mass% or more, more preferably 15 mass% or more, and particularly preferably 20 mass% or more, while it is preferably 300 mass% or less, more preferably 250 mass% or less, more preferably 200 mass% or less, more preferably 150 mass% or less, more preferably 100 mass% or less, more preferably 80 mass% or less, more preferably 50 mass% or less, and particularly preferably 40 mass% or less. The ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) may be, for example, 5% by mass or more and 300% by mass or less, 5% by mass or more and 250% by mass or less, 5% by mass or more and 200% by mass or less, 5% by mass or more and 150% by mass or less, 5% by mass or more and 100% by mass or less, 10% by mass or more and 80% by mass or less, 15% by mass or more and 50% by mass or less, or 20% by mass or more and 40% by mass or less.
[0027] The proportion of the phosphorus-based flame retardant (B) relative to the total mass of the resin composition is preferably 15% by mass or more, more preferably 17% by mass or more, and even more preferably 20% by mass or more, while it is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. If the proportion of the phosphorus-based flame retardant (B) is equal to or more than the lower limit, the flame retardancy is superior, and if it is equal to or less than the upper limit, the inherent physical properties of the thermoplastic resin (A) are easily expressed. The proportion of the phosphorus-based flame retardant (B) relative to the total mass of the present resin composition may be, for example, 15 mass% or more and 50 mass% or less, 17 mass% or more and 45 mass% or less, or 20 mass% or more and 40 mass% or less.
[0028] [Copolymer of α-olefin and unsaturated carboxylic acid (C)] The copolymer (C) enhances the dispersibility of the phosphorus-based flame retardant (B) in the thermoplastic resin (A). In the present invention, "copolymer (C) of an α-olefin and an unsaturated carboxylic acid" means a copolymer in which the proportion of α-olefin units relative to the total of 100 mol% of α-olefin units and unsaturated carboxylic acid units is 20 mol% or more and 80 mol% or less. In the copolymer (C), the ratio of the α-olefin units to the total of 100 mol% of the α-olefin units and the unsaturated carboxylic acid units is preferably 30 mol% or more, and on the other hand, 70 mol% or less. If the ratio of the α-olefin units is equal to or more than the lower limit, the compatibility with polyolefin resins is particularly excellent, and if it is equal to or less than the upper limit, the compatibility with the phosphorus-based flame retardant (B) is excellent.
[0029] In the copolymer (C), the α-olefin is preferably an α-olefin having 10 to 80 carbon atoms. If the α-olefin has 10 or more carbon atoms, compatibility with polyolefin resins in particular tends to be better, and if it has 80 or less carbon atoms, raw material costs tend to be better. The number of carbon atoms in the α-olefin is more preferably 12 to 70, and even more preferably 18 to 60.
[0030] In the copolymer (C), examples of the unsaturated carboxylic acid include (meth)acrylic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, glutaconic acid, norbornane-5-ene-2,3-dicarboxylic acid, and esters, anhydrides, imides, etc. of these unsaturated carboxylic acids. "(Meth)acrylic acid" refers to acrylic acid or methacrylic acid. Specific examples of the ester, anhydride or imide of an unsaturated carboxylic acid include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and glycidyl (meth)acrylate; dicarboxylic acid anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride; and maleimide compounds such as maleimide, N-ethylmaleimide, and N-phenylmaleimide. These may be used alone or in combination of two or more. Among the above, esters and dicarboxylic anhydrides are preferred from the viewpoint of copolymerization reactivity, and among these, dicarboxylic anhydrides are preferred from the viewpoint of compatibility with the phosphorus-based flame retardant (B), with maleic anhydride being particularly preferred.
[0031] The weight average molecular weight of the copolymer (C) is preferably at least 2,000, more preferably at least 3,000, and on the other hand, is preferably at most 50,000, more preferably at most 30,000. When the weight average molecular weight of the copolymer (C) is within the above upper and lower limit ranges, the dispersibility of the phosphorus-based flame retardant (B) is more excellent. The weight average molecular weight of the copolymer (C) may be, for example, 2,000 or more and 50,000 or less, or 3,000 or more and 30,000 or less. The weight average molecular weight of the copolymer (C) is a value calculated as standard polystyrene by dissolving the copolymer (C) in tetrahydrofuran (THF) and measuring the result by gel permeation chromatography.
[0032] Commercially available copolymers (C) include, for example, Lycorb CE2 (manufactured by Clariant Japan KK) and Diacalna 30M (manufactured by Mitsubishi Chemical Corporation).
[0033] As described above, the resin composition contains the copolymer (C), while the ratio of the copolymer (C) to the phosphorus-based flame retardant (B) is 10 mass % or less. In particular, the ratio of the copolymer (C) to the phosphorus-based flame retardant (B) (100% by mass) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.3% by mass or more, while being preferably 8% by mass or less, more preferably 6% by mass or less, and particularly preferably 5% by mass or less. By having the ratio of the copolymer (C) to the phosphorus-based flame retardant (B) (100% by mass) within the above range, a molded product having high flame retardancy can be obtained while maintaining high mechanical strength and high flexural modulus. The ratio of the copolymer (C) to the phosphorus-based flame retardant (B) (100 mass%) may be, for example, 0.01 mass% or more and 8 mass% or less, 0.05 mass% or more and 8 mass% or less, 0.1 mass% or more and 6 mass% or less, or 0.3 mass% or more and 5 mass%.
[0034] The proportion of copolymer (C) relative to the total mass of the resin composition is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.1% by mass or more, while it is preferably 1.2% by mass or less, more preferably 1.1% by mass or less, and even more preferably 1.0% by mass or less. If the proportion of copolymer (C) is equal to or greater than the lower limit, the phosphorus-based flame retardant (B) is well dispersed, and the flame retardancy and physical properties of the resin composition and the appearance of the molded product obtained are good. If the proportion of copolymer (C) is equal to or less than the upper limit, the influence of copolymer (C) on the flame retardancy of the resin composition can be suppressed. The proportion of copolymer (C) relative to the total mass of the present resin composition may be, for example, 0.01 mass% or more and 1.2 mass% or less, 0.03 mass% or more and 1.1 mass% or less, or 0.1 mass% or more and 1.0 mass% or less.
[0035] The proportion of the copolymer (C) relative to the total mass of the thermoplastic resin (A) and the phosphorus-based flame retardant (B) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, while it is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.0% by mass or less. If the proportion of the copolymer (C) is equal to or greater than the lower limit, the phosphorus-based flame retardant (B) is better dispersed, and the flame retardancy and physical properties of the resin composition and the appearance of the molded product obtained are better. If the proportion of the copolymer (C) is equal to or less than the upper limit, the effect of the copolymer (C) on the flame retardancy of the resin composition can be more suppressed. The ratio of the copolymer (C) to the total mass of the thermoplastic resin (A) and the phosphorus-based flame retardant (B) may be, for example, 0.01 mass% or more and 2.0 mass% or less, 0.05 mass% or more and 1.5 mass% or less, or 0.1 mass% or more and 1.0 mass% or less. The proportion of the combined mass of the thermoplastic resin (A), the phosphorus-based flame retardant (B) and the copolymer (C) relative to the total mass of the resin composition is preferably 10 mass% or more, more preferably 20 mass% or more, even more preferably 30 mass% or more, particularly preferably 40 mass% or more, and may be 100 mass%.
[0036] [Other flame retardants or flame retardant auxiliaries] The other flame retardants or flame retardant auxiliaries are preferably halogen-free organic or inorganic flame retardants or flame retardant auxiliaries, such as triazine ring-containing compounds, silicone flame retardants, metal hydroxides, metal oxides, boric acid compounds, and expandable graphite.
[0037] Examples of the triazine ring-containing compound include melamine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, and 1,3-hexylenedimelamine. Examples of silicone-based flame retardants include silicone oil, silicone rubber, and silicone resin. Examples of metal hydroxides include magnesium hydroxide, aluminum hydroxide, calcium hydroxide, barium hydroxide, zinc hydroxide, Kismer 5A (a trademark of magnesium hydroxide manufactured by Kyowa Chemical Industry Co., Ltd.), and the like. Examples of metal oxides include inorganic compounds such as zinc oxide, titanium oxide, aluminum oxide, magnesium oxide, titanium dioxide, and hydrotalcite, and surface-treated products thereof. Specific examples of metal oxides include TIPAQUE R-680 (titanium oxide trademark manufactured by Ishihara Sangyo Kaisha), Kyowamag 150 (magnesium oxide trademark manufactured by Kyowa Chemical Industry Co., Ltd.), DHT-4A (hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.), and Alcamizer 4 (zinc-modified hydrotalcite trademark manufactured by Kyowa Chemical Industry Co., Ltd.). An example of the boric acid compound is zinc borate. These flame retardants or flame retardant auxiliaries may be used alone or in combination of two or more.
[0038] [Other ingredients] The resin composition may contain at least one inorganic fiber filler (D) selected from the group consisting of glass fiber and carbon fiber. The inorganic fiber filler (D) may be used alone or in combination of two or more.
[0039] The type of glass fiber is not particularly limited, and any glass fiber such as E glass, C glass, S glass, or D glass can be used. The form of the glass fiber is not particularly limited, and any glass fiber such as chopped strand, roving, yarn, glass wool, etc. can be used, but chopped strand and glass wool are preferred from the viewpoint of workability.
[0040] The type of carbon fiber is not particularly limited, and any carbon fiber such as polyacrylonitrile (PAN)-based carbon fiber, pitch-based carbon fiber, graphite fiber, etc. can be used. The form of the carbon fiber is not particularly limited, and any carbon fiber such as filament, regular tow, large tow, stable yarn, chopped strand, etc. can be used, but chopped strand is preferred from the viewpoint of workability.
[0041] When the resin composition contains an inorganic fiber filler (D), the proportion of the inorganic fiber filler (D) relative to the total mass of the resin composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 25% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 3% by mass or less. If the proportion of the inorganic fiber filler (D) is equal to or more than the lower limit, it is easy to obtain a lip prevention effect and a smoke suppression effect, and if it is equal to or less than the upper limit, it is difficult to impair the inherent physical properties of the thermoplastic resin (A).
[0042] When the present resin composition contains an inorganic fiber filler (D), it may further contain an interfacial strength improver (E) for the inorganic fiber filler (D). As the interfacial strength improving agent (E), a polymer having an olefin skeleton (excluding polyolefin resin and copolymer (C)) is preferable, particularly from the viewpoint of compatibility with the thermoplastic resin (A) such as polyolefin resin. The interfacial strength is further improved by the compatibility of the olefin skeleton with the polyolefin resin.
[0043] The interfacial strength improving agent (E) preferably has an acidic group, and the interfacial strength is further improved by the reaction between the inorganic fibrous filler (D) and the acidic group. Examples of the acidic group include a carboxyl group, a carboxylic anhydride group, a sulfonic acid group, a sulfinic acid group, a phosphonic acid group, and a phosphinic acid group. At least one selected from the group consisting of a carboxyl group, a carboxylic anhydride group, a sulfonic acid group, a sulfinic acid group, a phosphonic acid group, and a phosphinic acid group is preferred, at least one selected from the group consisting of a carboxyl group, a carboxylic anhydride group, and a phosphonic acid group is more preferred, and at least one selected from the group consisting of a carboxyl group and a carboxylic anhydride group is particularly preferred.
[0044] Examples of the method for producing the interfacial strength improver (E) having an olefin skeleton and an acidic group include (1) a method in which an olefin resin is thermally decomposed at high temperature to reduce the molecular weight, and then a compound or monomer having an acidic group is added, (2) a method in which a low molecular weight olefin resin is polymerized, and then a compound or monomer having an acidic group is added, and (3) a method in which an α-olefin and a compound or monomer having an acidic group are copolymerized. As the polymerization method, radical polymerization methods such as solution polymerization, emulsion polymerization, suspension polymerization, and bulk polymerization, and living polymerization methods can be used. Furthermore, a method in which a macromonomer is once formed and then polymerized can also be used. Examples of compounds or monomers having an acidic group include acrylic acid, methacrylic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, etc., with maleic anhydride being particularly preferred.
[0045] Commercially available examples of the interfacial strength improver (E) include Eumex 1001 and 1010 (manufactured by Sanyo Chemical Industries, Ltd.), and Kayabrid 002PP and 003PP (manufactured by Kayaku Nouryon Co., Ltd.).
[0046] The present resin composition may contain at least one selected from the group consisting of antioxidants, ultraviolet absorbers, light stabilizers, and antiaging agents.
[0047] Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and thioether-based antioxidants. Examples of the phenol-based antioxidants include 2,6-di-tert-butyl-p-cresol, 2,6-diphenyl-4-octadecyloxyphenol, distearyl (3,5-di-tert-butyl-4-hydroxybenzyl)phosphonate, 1,6-hexamethylenebis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid amide], 4,4'-thiobis(6-tert-butyl-m-cresol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-butyl-m-cresol, ... 2,2'-ethylidenebis(6-tert-butyl-m-cresol), 2,2'-ethylidenebis(4,6-di-tert-butylphenol), 2,2'-ethylidenebis(4-sec-butyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, diethyl)-2,4,6-trimethylbenzene, 2-tert-butyl-4-methyl-6-(2-acryloyloxy-3-tert-butyl-5-methylbenzyl)phenol, stearyl (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate methyl]methane, thiodiethylene glycol bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,6-hexamethylene bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] ], bis[3,3-bis(4-hydroxy-3-tert-butylphenyl)butyric acid] glycol ester, bis[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl] terephthalate, 1,3,5-tris[(3,5-ditert-butyl-4-hydroxyphenyl)propionyloxyethyl] isocyanurate, 3,9-bis[1,1-dimethyl-2-{(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,10-tetraoxaspiro[5,5] undecane, triethylene glycol bis[(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], etc. The content of the phenol-based antioxidant is preferably 0.001 parts by mass or more, more preferably 0.05 parts by mass or more, per 100 parts by mass of the synthetic resin component in the resin composition, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.
[0048] Examples of phosphorus-based antioxidants include trisnonylphenyl phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl]phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, bis(2,4-ditert-butylphenyl)phosphite, phenyl)pentaerythritol diphosphite, bis(2,6-ditert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tritert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4'-n-butylidenebis(2-tert-butyl-5-methylphenol) hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite, tetrakis(2,4-ditert-butylphenyl)biphenylene diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4,6-tert-butylphenyl)-2-ethylhexyl phosphite, 2,2'-methylenebis(4,6-tert-butylphenyl)-2-ethylhexyl phosphite phenyl)-octadecyl phosphite, 2,2'-ethylidenebis(4,6-di-tert-butylphenyl)fluorophosphite, tris(2-[(2,4,8,10-tetrakis-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]ethyl)amine, phosphite of 2-ethyl-2-butylpropylene glycol and 2,4,6-tri-tert-butylphenol, tris(2,4-di-tert-butylphenyl)phosphite, and the like. The content of the phosphorus-based antioxidant is preferably 0.001 parts by mass or more, more preferably 0.05 parts by mass or more, per 100 parts by mass of the synthetic resin component in the resin composition, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.
[0049] Examples of the thioether antioxidants include dialkyl thiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, and pentaerythritol tetra(β-alkylthiopropionate esters). The content of the thioether-based antioxidant is preferably 0.001 parts by mass or more, more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the synthetic resin component in the resin composition, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.
[0050] Examples of the ultraviolet absorber include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone); 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'- 2-(2'-hydroxyphenyl)benzotriazoles such as 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-tert-octyl-6-(benzotriazolyl)phenol), and 2-(2'-hydroxy-3'-tert-butyl-5'-carboxyphenyl)benzotriazole; phenylsa Benzoates such as ricinate, resorcinol monobenzoate, 2,4-ditert-butylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, 2,4-ditert-amylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, hexadecyl-3,5-ditert-butyl-4-hydroxybenzoate; substituted oxanilides such as 2-ethyl-2'-ethoxyoxanilide, 2-ethoxy-4'-dodecyloxanilide; ethyl-α-cyano-β,β-diphenylacrylate, methyl cyanoacrylates such as aryl-2-cyano-3-methyl-3-(p-methoxyphenyl)acrylate; and triaryltriazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, and 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine. The content of the ultraviolet absorber is preferably 0.001 parts by mass or more, more preferably 0.05 parts by mass or more, and is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the synthetic resin component in the resin composition.
[0051] Examples of light stabilizers include 2,2,6,6-tetramethyl-4-piperidyl stearate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, and tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanol. tetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)-2-butyl-2-(3,5-ditert-butyl-4-hydroxybenzyl )malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-tert-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-tert-octylamino-s-triazine polycondensate, lysyl)amino)-s-triazin-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,2,6,Examples of the hindered amine compounds include 6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl)aminoundecane. The content of the light stabilizer is preferably 0.001 parts by mass or more, more preferably 0.05 parts by mass or more, and is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the synthetic resin component in the resin composition.
[0052] The present resin composition may contain fillers other than the inorganic fiber filler (D). As other fillers, fibrous, plate-like, granular, or powder-like fillers can be used. Specifically, inorganic fibrous reinforcing materials such as asbestos fibers, metal fibers, potassium titanate whiskers, aluminum borate whiskers, magnesium whiskers, silicon whiskers, wollastonite, sepiolite, asbestos, slag fibers, zonolite, elestadite, gypsum fibers, silica fibers, silica-alumina fibers, zirconia fibers, boron nitride fibers, silicon nitride fibers, and boron fibers, polyester fibers, nylon fibers, acrylic fibers, regenerated cellulose fibers, acetate fibers, kenaf, ramie, cotton, jute, hemp, sisal, flax, linen, Examples of the fillers include organic fibrous reinforcing materials such as silk, Manila hemp, sugar cane, wood pulp, waste paper, waste paper, and wool, and plate-like or granular reinforcing materials such as glass flakes, non-swelling mica, graphite, metal foil, ceramic beads, clay, mica, sericite, zeolite, bentonite, dolomite, kaolin, finely powdered silicic acid, feldspar powder, potassium titanate, silicic balloons, calcium carbonate, magnesium carbonate, barium sulfate, calcium oxide, aluminum oxide, titanium oxide, titanium dioxide, aluminum silicate, gypsum, novaculite, dawsonite, and white clay. These fillers may be coated or bundled with a thermoplastic resin such as an ethylene-vinyl acetate copolymer or a thermosetting resin such as an epoxy resin, or may be treated with a coupling agent such as an aminosilane or an epoxysilane. The content of the other filler is preferably 10 parts by mass or more, and more preferably 20 parts by mass or more, per 100 parts by mass of the synthetic resin component in the resin composition, and is preferably 60 parts by mass or less, and more preferably 50 parts by mass or less.
[0053] The present resin composition may contain a crystal nucleating agent. As the crystal nucleating agent, any of those generally used as a crystal nucleating agent for polyolefin resins can be used appropriately, including, for example, inorganic crystal nucleating agents and organic crystal nucleating agents.
[0054] Specific examples of inorganic crystal nucleating agents include kaolinite, synthetic mica, clay, zeolite, graphite, carbon black, magnesium oxide, titanium oxide, calcium sulfide, boron nitride, calcium carbonate, barium sulfate, aluminum oxide, neodymium oxide, and metal salts such as phenylphosphonate, etc. These inorganic crystal nucleating agents may be modified with an organic substance in order to enhance dispersibility in the composition.
[0055] Specific examples of organic crystal nucleating agents include sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, potassium terephthalate, calcium oxalate, sodium laurate, potassium laurate, sodium myristate, potassium myristate, calcium myristate, sodium octacosanoate, calcium octacosanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium toluate, sodium salicylate, potassium salicylate, salicylic acid Examples of the organic carboxylic acid metal salts include zinc, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalate, and sodium cyclohexanecarboxylate; organic sulfonates such as sodium p-toluenesulfonate and sodium sulfoisophthalate; carboxylic acid amides such as stearic acid amide, ethylene bislauric acid amide, palmitic acid amide, hydroxystearic acid amide, erucic acid amide, and trimesic acid tris(t-butylamide); benzylidene sorbitol and derivatives thereof; phosphorus compound metal salts such as sodium 2,2'-methylenebis(4,6-di-t-butylphenyl)phosphate; and sodium 2,2-methylbis(4,6-di-t-butylphenyl).
[0056] The present resin composition may contain a plasticizer. As the plasticizer, any plasticizer generally used for polyolefin resins can be used as appropriate, such as polyester-based plasticizers, glycerin-based plasticizers, polycarboxylic acid ester-based plasticizers, polyalkylene glycol-based plasticizers, and epoxy-based plasticizers. These plasticizers may be used alone or in combination of two or more kinds.
[0057] Specific examples of polyester-based plasticizers include polyesters composed of an acid component such as adipic acid, sebacic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, rosin, etc., and a diol component such as propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, ethylene glycol, diethylene glycol, etc., and polyesters composed of hydroxycarboxylic acids such as polycaprolactone, etc. These polyesters may be end-capped with a monofunctional carboxylic acid or a monofunctional alcohol, or may be end-capped with an epoxy compound, etc.
[0058] Specific examples of the glycerin-based plasticizer include glycerin monoacetomonolaurate, glycerin diacetomonolaurate, glycerin monoacetomonostearate, glycerin diacetomonooleate, and glycerin monoacetomonomonoacetate.
[0059] Specific examples of polyvalent carboxylate ester plasticizers include phthalates such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, diheptyl phthalate, dibenzyl phthalate, and butyl benzyl phthalate; trimellitates such as tributyl trimellitate, trioctyl trimellitate, and trihexyl trimellitate; adipic esters such as diisodecyl adipate, n-octyl-n-decyl adipate, methyl diglycol butyl diglycol adipate, benzyl methyl diglycol adipate, and benzyl butyl diglycol adipate; citric esters such as triethyl acetyl citrate and tributyl acetyl citrate; azelaic esters such as di-2-ethylhexyl azelaate; and sebacate esters such as dibutyl sebacate and di-2-ethylhexyl sebacate.
[0060] Specific examples of polyalkylene glycol plasticizers include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) block and / or random copolymers, polytetramethylene glycol, ethylene oxide addition polymers of bisphenols, propylene oxide addition polymers of bisphenols, and tetrahydrofuran addition polymers of bisphenols, as well as end-blocking compounds such as terminal epoxy-modified compounds, terminal ester-modified compounds, and terminal ether-modified compounds.
[0061] Epoxy plasticizers generally refer to epoxy triglycerides made from alkyl epoxy stearates and soybean oil, but other types of plasticizers, such as epoxy resins made mainly from bisphenol A and epichlorohydrin, can also be used.
[0062] Specific examples of other plasticizers include benzoic acid esters of aliphatic polyols such as neopentyl glycol dibenzoate, diethylene glycol dibenzoate, and triethylene glycol di-2-ethyl butyrate, fatty acid amides such as stearic acid amide, aliphatic carboxylic acid esters such as butyl oleate, oxyacid esters such as methyl acetylricinoleate and butyl acetylricinoleate, pentaerythritol, various sorbitols, polyacrylic acid esters, and paraffins.
[0063] The present resin composition may contain a fluorine-containing anti-dripping agent. The fluorine-containing anti-dripping agent may be a fluorine-containing polymer having fibril-forming ability. Such fluorine-containing polymer may be polytetrafluoroethylene (hereinafter, also referred to as "PTFE"), a tetrafluoroethylene copolymer (e.g., a tetrafluoroethylene / hexafluoropropylene copolymer), a partially fluorinated polymer as shown in U.S. Pat. No. 4,379,910, a polycarbonate resin produced from a fluorinated diphenol, etc. Among them, PTFE is preferred.
[0064] PTFE having fibril-forming ability has an extremely high molecular weight, and shows a tendency to bond PTFE to each other and become fibrous due to external action such as shear force, etc. The molecular weight is preferably 1 million or more, more preferably 2 million or more, in terms of number average molecular weight calculated from the standard specific gravity, while it is preferably 10 million or less, more preferably 9 million or less. The fibril-forming PTFE can be used in the form of an aqueous dispersion in addition to a solid form.
[0065] Commercially available PTFE products having fibril-forming ability include, for example, Teflon (registered trademark) 6J manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd., and Polyflon (registered trademark) MPA FA500 and F-201L manufactured by Daikin Industries, Ltd. Commercially available aqueous dispersions of PTFE include Fluon AD-939E manufactured by Asahi ICI Fluoropolymers Co., Ltd., Fluon D-310 and D-210C manufactured by Daikin Industries, Ltd., and Teflon 31JR manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd.
[0066] In order to improve the dispersibility of the fibril-forming PTFE in the resin composition and obtain even better flame retardancy, mechanical properties, and flexural modulus, it is also possible to use a PTFE mixture in the form of a mixture of the fibril-forming PTFE and other resins. The proportion of PTFE relative to the total mass of the PTFE mixture is preferably 1 mass% or more, more preferably 5 mass% or more, and is preferably 60 mass% or less, more preferably 55 mass% or less. When the proportion of PTFE is within this range, good dispersibility of PTFE can be achieved.
[0067] The PTFE mixture can be prepared, for example, by a method of: (1) mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of another resin and co-precipitating to obtain a co-agglomerated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.); (2) mixing an aqueous dispersion of PTFE with dried particles of another resin (method described in JP-A-4-272957); or (3) uniformly mixing an aqueous dispersion of PTFE with a solution of another resin and simultaneously extracting each medium from the mixture. (4) a method of polymerizing a monomer that forms another resin in an aqueous dispersion of PTFE (method described in JP-A-09-95583), or (5) a method of uniformly mixing an aqueous dispersion of PTFE and a dispersion of another resin, polymerizing a vinyl monomer in the resulting mixed dispersion, and then obtaining a mixture (method described in JP-A-11-29679, etc.) can be used. Commercially available PTFE mixtures include "Metabrene A3000" from Mitsubishi Chemical Corporation and "BLENDEX B449" from GE Specialty Chemicals.
[0068] The content of the fluorine-containing drip prevention agent is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, in terms of the amount of PTFE per 100 parts by mass of the resin composition, while being preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.5 parts by mass or less.
[0069] In addition to the above, the resin composition may contain additives that are usually used in synthetic resins, such as crosslinking agents, antistatic agents, metal soaps, filling agents, antifogging agents, anti-plateout agents, surface treatment agents, fluorescent agents, antifungal agents, bactericides, foaming agents, metal deactivators, release agents, pigments, processing aids, and the like, within the range that does not impair the effects of the present invention.
[0070] [Method of producing resin composition] Any method may be used to produce the resin composition, for example, a method in which the thermoplastic resin (A), the phosphorus-based flame retardant (B), the copolymer (C), and, if necessary, other flame retardants, flame retardant auxiliaries, and other components are thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and optionally granulated using an extrusion granulator or a briquetting machine, and then melt-kneaded and extruded using a melt kneader. Examples of the melt kneader include a twin-screw extruder such as a vented twin-screw extruder, a Banbury mixer, a kneading roll, a single-screw extruder, and a multi-screw extruder having three or more screws. The temperature during melt kneading is, for example, 170 to 260°C. The resin composition extruded as described above is either directly cut into pellets by a machine such as a pelletizer, or cooled to form strands, and then the strands are cut into pellets by a machine such as a pelletizer.
[0071] The resin composition described above contains the copolymer (C) in addition to the thermoplastic resin (A) and the phosphorus-based flame retardant (B), and therefore can exhibit excellent flame retardancy while fully maintaining the inherent physical properties (e.g., mechanical strength and flexural modulus) of the polyolefin resin (A). The copolymer (C) improves the dispersibility of the phosphorus-based flame retardant (B) in the thermoplastic resin (A) such as a polyolefin resin. It is believed that the improved dispersibility of the phosphorus-based flame retardant (B) makes it easier to form char during combustion, improving flame retardancy. The mechanism behind this is unclear, but the following is thought to be the cause. In particular, when the thermoplastic resin (A) is a polyolefin resin, the polyolefin resin is classified as a low-polarity resin among thermoplastic resins, and it is difficult to disperse a polar additive such as the phosphorus-based flame retardant (B). On the other hand, the copolymer (C) has an α-olefin moiety with low polarity that has excellent compatibility with the polyolefin resin, and an unsaturated carboxylic acid moiety with polarity that has excellent compatibility with the phosphorus-based flame retardant (B). It is considered that the presence of the copolymer (C) between the polyolefin resin and the phosphorus-based flame retardant (B) during melt-kneading of the resin composition improves the dispersibility of the phosphorus-based flame retardant (B) in the polyolefin resin.
[0072] The effects of the copolymer (C) include (1) improving the dispersibility of the phosphorus-based flame retardant (B) (finely dispersing), (2) promoting char generation during combustion, and (3) improving physical properties (tensile strain at break). Specifically, when a flat test piece obtained by molding a resin composition containing a thermoplastic resin (A) and a phosphorus-based flame retardant (B) is heated with a burner, small and numerous chars are formed on the surface if the resin composition does not contain copolymer (C), but the size of the chars increases and the heat transfer suppression effect is improved if the resin composition contains copolymer (C). In a cone calorimeter test, when a 3 mm thick flat test piece obtained by molding a resin composition containing a thermoplastic resin (A) and a phosphorus-based flame retardant (B) is burned by radiant heat, many gaps in the char are generated and the molded body burns if the resin composition does not contain copolymer (C), but when the resin composition contains copolymer (C), the gaps in the char are reduced and char is formed by burning the sides, resulting in a dome shape. Although the mechanism is unclear, the addition of copolymer (C) forms a stronger char, suppressing heat transfer and enabling the material to achieve a V-0 rating in the UL94 test. The copolymer (C) can exert the above effects even in a small amount (for example, 1.2 mass % or less based on the total mass of the resin composition).
[0073] According to the present resin composition, since the phosphorus-based flame retardant (B) is well dispersed, it is possible to obtain a molded article having a dispersibility calculated by the following formula of, for example, 22% or less, or even 21% or less. Dispersibility [%]=4,000μm 2 The sum of the area values of particles of size 100 μm 2 ]÷Flame retardant area (threshold 3%, 136,331) [μm 2 ] x 100 Here, 4,000 μm 2 The total area of the particles of the above sizes and the flame retardant area are determined by image processing of an optical microscope image of the molded article, as described in detail in the Examples below.
[0074] [Molded body] A molded article according to one embodiment of the present invention is made of the present resin composition. The shape of the molded product is not particularly limited, and may be in various shapes such as a resin plate, sheet, film, cable, or irregular shape.
[0075] The molded article can be obtained by molding the present resin composition. The molding method is not particularly limited, and examples thereof include extrusion, calendaring, injection molding, rolling, compression molding, blow molding, and the like. The temperature at which the present resin composition is molded is, for example, 170 to 260°C. EXAMPLES
[0076] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following examples, % is based on mass unless otherwise specified. Evaluations were performed on the following items.
[0077] (1) Flame retardant (UL94) The flame retardancy of the obtained molded articles (1 / 16 inch test bars) was judged in accordance with the UL94 standard.
[0078] (2) Flame retardant dispersion evaluation 1 The number of undispersed flame retardants present in the obtained molded product (0.5 mm thick sheet) was evaluated. The evaluation procedure involved observing the sheet at 50x magnification (10x eyepiece, 5x objective) using an optical microscope (Nikon, product name: ECLIPSE E600W POL) with transmitted light. From this optical microscope image, five 640 x 480 pixel images were randomly selected, imported, and converted to 8-bit format using image processing software (Image J, Ver 1.52a). When observed at 50x, 1,000 μm is 260 pixels, so 640 x 480 pixels is 4,454,379 μm. 2 The flame retardant in the sheet was then highlighted by bandpass filtering, and the concentration was measured. Because the flame retardant has the highest contrast in the image, the area where the binarized area value is 3% from the minimum value (0) was set as the threshold value, and the flame retardant area was extracted. Next, particles in the binarized image with a size of 4,000 μm were extracted. 2 The particle areas of the above sizes were totaled, and the dispersibility [%] was calculated using the formula below, and the average dispersibility for each of the five images was calculated. Dispersibility [%]=4,000μm 2 The sum of the area values of particles of size 100 μm 2 ]÷Flame retardant area (threshold 3%, 136,331) [μm 2 ] x 100
[0079] (3) Flame retardant dispersion evaluation 2 From the images observed in the same manner as in (2) Evaluation of Dispersibility of Flame Retardants 1, the dispersibility was compared according to the following criteria. A: More than 100 flame retardant particles are observed in the photograph. B: There are 50 or more but less than 100 flame retardant particles in the photograph. C: There are less than 50 flame retardant particles in the photograph. D: There are less than 30 flame retardant particles in the photograph. In this evaluation, the degree of dispersibility increases from A to D. (4) Bending properties The obtained molded product (JIS K7139-A1 dumbbell test piece) was cut to a length of 80 mm, and the flexural modulus (GPa) was measured in accordance with JIS K7171.
[0080] (5) Tensile properties The obtained molded bodies (JIS K7139-A1 dumbbell test pieces) were used to measure the tensile strength at yield (MPa) and the tensile strain at break (%) in accordance with JIS K7161-1.
[0081] (6) Combustion heat value (cone calorimeter) Test pieces measuring 100 mm x 100 mm x 3 mm thick were subjected to a radiant heat test of 50 kW / m using a Toyo Seiki Co., Ltd. C3 Cone Calorimeter III in accordance with ISO 5660-1 (2002). 2 Under the condition, the maximum heat generation rate (kW / m 2 ), total heat output (MJ / m 2 ) was measured.
[0082] The following raw materials were used: <Polyolefin resin> A-1: Polypropylene resin (Japan Polypropylene Corporation, Novatec PP FY-4, melt mass flow rate 5 g / 10 min). A-2: Polypropylene resin (Japan Polypropylene Corporation, Novatec PP SA06GA, melt mass flow rate 60 g / 10 min). <Flame retardants> B: Phosphorus-based flame retardant composition (ADEKA CORPORATION, Adeka STAB FP-2200, containing 50-60% piperadine pyrophosphate, 35-45% melamine pyrophosphate, and 3-6% zinc oxide based on the total mass of the phosphorus-based flame retardant composition).
[0083] <Dispersant> C-1: α-olefin-maleic anhydride copolymer (Mitsubishi Chemical Corporation, Diacarna 30M, weight average molecular weight 7,800). C-2: α-olefin-maleic anhydride copolymer (Clariant Japan Ltd., Lycorb CE2, weight average molecular weight 13,500). C-3: Maleic anhydride modified polyethylene (Hiwax 1105A, manufactured by Mitsui Chemicals, Inc.). C-4: Acid-modified polyethylene (Clariant Japan Ltd., Recorb H12).
[0084] [Examples 1 to 7, Comparative Examples 1 to 4] The raw materials shown in Table 1 were blended in the ratios shown in Table 1 and mixed by hand blending. Then, using a φ30 mm co-rotating twin screw extruder (model name "BT-30", manufactured by Plastics Engineering Research Institute Co., Ltd., L / D=30), the mixture was melt-kneaded at a screw rotation speed of 250 rpm and a cylinder temperature of 200°C to obtain a resin composition. "L / D" indicates the ratio of the screw length (L) to the screw diameter (D).
[0085] The obtained resin composition was injection molded at a molding temperature of 200°C using a 100t injection molding machine (model name "SE-100DU", manufactured by Sumitomo Heavy Industries, Ltd.) to obtain a molded body (1 / 16 inch test bar). This molded body (1 / 16 inch test bar) was used as a test piece for UL94 evaluation. The obtained resin composition was injection molded at a molding temperature of 200° C. using a 100 ton injection molding machine (model name "SE-100DU", manufactured by Sumitomo Heavy Industries, Ltd.) to obtain a molded body (JIS K7139-A1 dumbbell test piece). This molded body (JIS K7139-A1 dumbbell test piece) was used as a test piece for evaluating bending properties and tensile properties.
[0086] The resin composition obtained was injection molded at a molding temperature of 200°C using a 100t injection molding machine (model name "SE-100DU", manufactured by Sumitomo Heavy Industries, Ltd.) to obtain a molded body (100 x 100 x 3 mm square plate). This molded body (100 x 100 x 3 mm square plate) was pressed at a molding temperature of 200°C and a molding pressure of 10 MPa using a hydraulic molding machine (manufactured by Shoji Iron Works, Ltd.) in a sequence of preheating for 5 minutes, pressing for 5 minutes, and cooling for 5 minutes to obtain a molded body (sheet) with a thickness of 0.5 mm. This molded body (sheet) was used as a test piece for evaluating the dispersibility of the flame retardant.
[0087] The properties of these molded products were measured, and the results are shown in Table 1. With regard to dispersibility, Examples 1 to 7 and Comparative Examples 1 to 3 were evaluated as Dispersibility Evaluation 1, and Example 4 and Comparative Examples 1 and 4 were evaluated as Dispersibility Evaluation 2. In addition, the ratios (%) of the dispersibility (values obtained in dispersibility evaluation 1), bending modulus, and tensile breakage strain of each Example and Comparative Example to the dispersibility (values obtained in dispersibility evaluation 1), bending modulus, and tensile breakage strain of Comparative Example 1 were calculated. These values are shown in Table 1 as dispersibility ratio, bending modulus ratio, and tensile breakage strain.
[0088] [Example 8] The composition was A-2: Novatec PP, SA06GA 39.18% by mass as polypropylene resin, B: ADK STAB FP-2200 58.78% by mass as phosphorus-based flame retardant composition, C-1: Diacarna 30M 1.96% by mass as dispersant, and ADK STAB AO-60, 2112 0.04% by mass each as antioxidant. The flame retardant masterbatch-1 was produced by melt-kneading using a φ30mm co-rotating twin-screw extruder (model name "BT-30", manufactured by Plastics Engineering Research Institute Co., Ltd., L / D=30) at a screw rotation speed of 250 rpm and a cylinder temperature of 200°C. This master batch-1 was mixed with 50% by mass of polypropylene resin A-1 Novatec PP FY4 at 50% by mass, and injection molded at a molding temperature of 200°C using a 100t injection molding machine (model name "SE-100DU", manufactured by Sumitomo Heavy Industries, Ltd.), and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0089] [Example 9] A master batch-2 was obtained under the same conditions as in Example 8, except that the polypropylene resin A-2: Novatec PP, SA06GA was 29.31% by mass, the phosphorus-based flame retardant composition B: Adeka STAB FP-2200 was 68.39% by mass, the dispersant C: Diacarna 30M was 2.25% by mass, and the antioxidants Adeka STAB AO-60 and 2112 were 0.03% by mass. The obtained master batch-2 was mixed with 47% by mass of polypropylene resin A-1 Novatec PP FY4 at 53% by mass, and then injection molded under the same conditions as in Example 8, and the same evaluation as in Example 1 was performed. The obtained results are shown in Table 1.
[0090] [Table 1]
[0091] In Table 1, B / A is the ratio (%) of phosphorus-based flame retardant (B) to thermoplastic resin (A) (100%). C / B is the ratio (%) of copolymer (C) to phosphorus-based flame retardant (B) (100%) (same below).
[0092] The molded articles of the resin compositions of Examples 1 to 9 containing the copolymer (C) (C-1 or C-2) of α-olefin and unsaturated carboxylic acid were superior in flame retardancy and dispersibility of the flame retardant compared to the molded article of the resin composition of Comparative Example 1 not containing the copolymer (C). In addition, sufficient flexural modulus and tensile yield strength were exhibited, and further, the tensile breaking strain was improved due to the improved dispersibility of the flame retardant. Moreover, in Examples 1 to 9, the test results according to the UL94 standard were all V-0, which shows that the resin compositions of Examples 1 to 9 are resin compositions that are inhibited from dripping during combustion.
[0093] On the other hand, the molded article of the resin composition of Comparative Example 2, which contains maleic anhydride-modified polyethylene instead of copolymer (C), has excellent flame retardancy but poor dispersibility of the flame retardant. It is also found that the tensile strain ratio at break is small and the mechanical strength is poor. The molded article of the resin composition of Comparative Example 3, in which the acid-modified polyethylene was blended instead of the copolymer (C), was inferior in flame retardancy and dispersibility of the flame retardant. In addition, the tensile strain ratio at break was small, and it is understood that the mechanical strength was inferior. In Comparative Example 4, in which the ratio of copolymer (C) to phosphorus-based flame retardant (B) was too high, the dispersion of the flame retardant was better than in Example 4, but the flexural modulus was significantly reduced, indicating that the inherent properties of polypropylene were significantly impaired.
[0094] [Comparative test of combustion heat generation using a cone calorimeter] The raw materials shown in Table 2 were blended in the ratios shown in Table 2 and mixed by hand blending. Then, using a φ30 mm co-rotating twin screw extruder (model name "BT-30", manufactured by Plastics Engineering Research Institute Co., Ltd., L / D=30), the mixture was melt-kneaded at a screw rotation speed of 250 rpm and a cylinder temperature of 200°C to obtain a resin composition. For the obtained resin composition, a test piece for evaluating the dispersibility of the flame retardant was prepared in the same manner as in Example 1, and dispersibility evaluation 1 was performed to determine the dispersibility and dispersibility ratio. The results are shown in Table 2. The resin composition thus obtained was injection molded at a molding temperature of 200°C using a 100t injection molding machine (model name "SE-100DU", manufactured by Sumitomo Heavy Industries, Ltd.) to obtain a molded product (a square plate of 100 x 100 x 3 mm). The combustion heat value of the molded product thus obtained was evaluated using a cone calorimeter. The results are shown in Table 2.
[0095] [Table 2]
[0096] In comparison of the combustion heat release amount using a cone calorimeter shown in Table 2, Examples 3, 10, and 11, which contained the copolymer (C) (C-1 or C-2) of an α-olefin and an unsaturated carboxylic acid, had lower total heat release amount and maximum heat release rate and were more flame retardant than Comparative Examples 1 and 5, which did not contain the copolymer (C). [Industrial Applicability]
[0097] According to the resin composition of the present invention, a molded article having excellent flame retardancy, mechanical strength and flexural modulus can be obtained, in which the phosphorus-based flame retardant is well dispersed. The molded article obtained using the resin composition of the present invention has excellent flame retardancy, mechanical strength and flexural modulus, and can be suitably used as a molding material, cable, etc. in the fields of automobiles, office automation equipment such as printers, and electric and electronic fields such as mobile phones.
Claims
1. The present invention comprises a thermoplastic resin (A), a phosphorus-based flame retardant (B), and a copolymer (C) of an α-olefin and an unsaturated carboxylic acid, The thermoplastic resin (A) is a polyolefin resin, the phosphorus-based flame retardant (B) is a salt of (poly)phosphoric acid and a nitrogen compound, and the nitrogen compound contains melamine or piperazine; The ratio of the phosphorus-based flame retardant (B) to the thermoplastic resin (A) is 5% by mass or more and 400% by mass or less, A resin composition, wherein the ratio of the copolymer (C) to the phosphorus-based flame retardant (B) is 10 mass% or less.
2. The resin composition according to claim 1, wherein the proportion of the thermoplastic resin (A) relative to the total mass of the resin composition is 20 mass% or more and 85 mass% or less.
3. 3. The resin composition according to claim 1, wherein the copolymer (C) is a copolymer of an α-olefin and maleic anhydride.
4. The resin composition according to any one of claims 1 to 3, wherein the α-olefin in the copolymer (C) has 10 or more and 80 or less carbon atoms.
5. The resin composition according to any one of claims 1 to 4, wherein in the copolymer (C), a ratio of the α-olefin units to a total of 100 mol% of the α-olefin units and the unsaturated carboxylic acid units is 30 mol% or more and 70 mol% or less.
6. The resin composition according to any one of claims 1 to 5, wherein the weight average molecular weight of the copolymer (C) is 2,000 or more and 50,000 or less.
7. The resin composition according to any one of claims 1 to 6, further comprising a metal oxide.
8. The resin composition according to claim 7 , wherein the metal oxide comprises zinc oxide.
9. A molded article made of the resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Composite intumescent flame retardant inflaming retarding general polypropylene and preparation method thereof
CN103087414A
Electromagnetic wave shielding resin composition
JP2002129003A
Thermoplastic resin composition, resin pellet made therefrom, and process for producing injection molded article
JP2002146204A
Flame-retardant polyolefin resin composition and its molded article
JP2005029628A
Thermoplastic resin composition
JP2007016093A